2017
DOI: 10.4172/2157-7110.1000672
|View full text |Cite
|
Sign up to set email alerts
|

Breast and Thigh Meat Chemical Composition and Fatty Acid Profile in Broilers Fed Diet with Dietary Fat Sources

Abstract: Experiment was conducted to evaluate effects of different fat sources on breast and thigh meat chemical composition and fatty acid profile in broilers. Treatments were 1) DF1: basal diet + soybean oil; 2) DF2: basal diet + chicken fat; 3) DF2: basal diet + tallow; 4) DF3: basal diet + tallow and lard, and 5) DF5: basal diet + lard. Addition of different fat sources had no significant impact on relative organ weight (P>0.05). Breast meat crude fat content was suppressed in DF1 and DF5 relative to DF4 (P<0.05). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…Some of the most important nutritional aspects are the lipid content and FA profile. It is well documented that the lipid contents and fatty acid profiles of broiler chicken meat and livers can be altered by the feed intake of the birds [45,46,47,48]. Changes in FA profiles, especially decreased SFAs and increased PUFAs, would alleviate criticism by improving nutritional value and would play a key role in improving quality [49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the most important nutritional aspects are the lipid content and FA profile. It is well documented that the lipid contents and fatty acid profiles of broiler chicken meat and livers can be altered by the feed intake of the birds [45,46,47,48]. Changes in FA profiles, especially decreased SFAs and increased PUFAs, would alleviate criticism by improving nutritional value and would play a key role in improving quality [49].…”
Section: Discussionmentioning
confidence: 99%
“…According to Pinchasov and Nir [31], PUFAs can inhibit the synthesis of MUFAs through the inhibition of 9-desaturase enzyme complex activity, which is the main enzyme responsible for the conversion of SFAs to MUFAs. Long-chain n-3 fatty acids are well known for their health benefits to humans and animals, such as lowering circulating cholesterol concentrations and reducing the risk of heart disease [47]. Notably, TM oil supplementation significantly increased the n-3 and n-3 PUFA concentrations in the liver in comparison with palm oil and poultry fat supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fat-based feedbacks such as soyabean oil, rapeseed oil, and other processed fat products did not affect the chemical composition of chicken meat. Bostami et al (2017) also reported that the chemical composition of broiler meat was not affected by different dietary fat sources, unless for crude fat in breast meat. Candlenut kernel oil in T3 group had the highest content of fat (36.61%) than control (31.02%).…”
Section: Discussionmentioning
confidence: 96%
“…This is because meat is seen to be a major source of fat in the diet and especially of saturated fatty acids, which have been implicated in diseases associated with modern life (Wood et al, 2003). Among the nutritional aspects of food, lipid content and fatty acid profile are the most important factors (Bostami et al, 2017). Fat and fatty acids in muscle and adipose tissues are among the major factors that influence meat quality, particularly nutritional value and palatability (Coetzee and Hoffman, 2002).…”
Section: Introductionmentioning
confidence: 99%